2014
DOI: 10.1002/eji.201343744
|View full text |Cite
|
Sign up to set email alerts
|

Differential IL‐10 production by DCs determines the distinct adjuvant effects of LPS and PTX in EAE induction

Abstract: Pertussis toxin (PTX) is used as an adjuvant to induce EAE in mice as a model of MS. Although LPS and PTX are similar in their ability to mature dendritic cells (DCs) and in their adjuvant properties, here we demonstrate that LPS does not induce EAE development. We also demonstrate that DCs treated with PTX (PTX-DCs) are able to induce EAE, whereas DCs treated with LPS (LPS-DCs) fail to induce EAE. We determine that a key difference between LPS-DCs and PTX-DCs is that LPS-DCs produce larger amounts of IL-10. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 43 publications
(68 reference statements)
1
11
0
Order By: Relevance
“…number of lymphocytes and macrophages, which secrete several cytokines after inflammatory stimulation. TNF-α, IL-1β, and IL-6 are major inflammatory cytokines released by classically activated macrophages, while IL-10 produced by Th2 cells and alternatively activated macrophages is anti-inflammatory [26,34]. In our study, the supernatants of splenocytes contained significantly reduced levels of TNF-α, IL-1β and IL-6 in cultures from mice from the HQGP-treated group, while levels of IL-10 were upregulated.…”
Section: Ns Hqgpsupporting
confidence: 51%
“…number of lymphocytes and macrophages, which secrete several cytokines after inflammatory stimulation. TNF-α, IL-1β, and IL-6 are major inflammatory cytokines released by classically activated macrophages, while IL-10 produced by Th2 cells and alternatively activated macrophages is anti-inflammatory [26,34]. In our study, the supernatants of splenocytes contained significantly reduced levels of TNF-α, IL-1β and IL-6 in cultures from mice from the HQGP-treated group, while levels of IL-10 were upregulated.…”
Section: Ns Hqgpsupporting
confidence: 51%
“…Disease in PTX-treated mice was otherwise indistinguishable from that in mice that did not receive PTX (not shown). The mechanism by which it promotes disease induction is not yet clear, but we ( 37 ) and others ( 36 , 39 ) have shown that PTX has innate immunomodulatory effects. Therefore, PTX may act as a surrogate for environmental factors that promote development of CNS autoimmune disease.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, BMDCs overexpressing Nr4a2 have a tolerogenic phenotype by virtue of which they are able to induce tolerance in the EAE mice model and prevent its development. Tolerogenic DCs regulate tolerance, in part, by promoting the expansion of Treg cells and/or attenuating T H 1/T H 17 responses that contribute to the pathogenesis of several inflammatory disorders, including EAE . To determine if Nr4a2‐induced tolerogenic DCs regulate the expansion of Treg cells, we isolated cells from spleen and looked at the percentage of Treg cells by analyzing the Foxp3 expression using FACS.…”
Section: Resultsmentioning
confidence: 99%